2012
DOI: 10.1111/papr.12014
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Gabapentin Enacarbil in Subjects with Neuropathic Pain Associated with Diabetic Peripheral Neuropathy

Abstract: Overall, none of the GEn treatment groups differentiated from placebo. Analyses of the secondary endpoints showed comparable results across treatment groups. However, the majority of the endpoints, including all of the pain endpoints, showed the largest numerical treatment difference was between GEn 3,600 mg and placebo. The active control, PGB (300 mg/day), did not differentiate from placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 16 publications
3
58
0
Order By: Relevance
“…Extended-release formulations of gabapentin (gabapentin extended release or enacarbil) have similar efficacy as gabapentin in clinical trials and can be used twice daily. 41,73 Similar efficacy as compared to TCA has been reported. 9,48 Common side effects include somnolence, dizziness, and weight gain.…”
Section: Pregabalin and Gabapentinsupporting
confidence: 59%
“…Extended-release formulations of gabapentin (gabapentin extended release or enacarbil) have similar efficacy as gabapentin in clinical trials and can be used twice daily. 41,73 Similar efficacy as compared to TCA has been reported. 9,48 Common side effects include somnolence, dizziness, and weight gain.…”
Section: Pregabalin and Gabapentinsupporting
confidence: 59%
“…[18][19][20][21][22][23][24][25][26] Five studies were carried out in the United States; 18,19,21,23,25 two in Europe, Australia, and South Africa; 20,22 one in Japan; 24 and one across 67 sites in 11 countries. 26 Eight studies 18,19,[21][22][23][24][25][26] reported patient ethnic information: about 71% of the overall study population was Caucasian. We are aware of two RCTs conducted by Pfizer (Pfizer protocols A0081071 and A0081030), which were cited in a review 33 but which have apparently not been published.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Numerous randomized controlled trials (RCTs) [18][19][20][21][22][23][24] have shown pregabalin to alleviate daily pain associated with DPN significantly more than placebo, but two RCTs 25,26 demonstrated no significant difference in pain alleviation between pregabalin and placebo, and some RCTs 20,22,[24][25][26] have reported similar proportions of patients on pregabalin or placebo who experience at least 50% pain reduction. These studies have also reported conflicting outcomes about safety.…”
mentioning
confidence: 98%
“…The results obtained showed Gabapentin is an effective drug for the treatment of neuropathic pain and has been reported to be effective in various diseases including trigeminal neuralgia, postherpetic neuralgias, and diabetic neuropathy [11,12,16]. The recommended and tolerable dosage of gabapentin in the literature is reported between 900 and 3600 mg per day [17].…”
Section: Discussionmentioning
confidence: 99%
“…Gabapentin has shown to have a beneficial role in central and peripheric neuropathic pain, in placebo-controlled, randomized, double-blind several studies [12,13]. However, the number of the studies which shows beneficial effects of gabapentin on CTS is limited.…”
mentioning
confidence: 99%